Senam Kaki dan Stimulasi Kutaneus terhadap Kelembaban Kulit pada Diabetisi - I Made Sukarja; I Wayan Sukawana; Ni Made Wedri (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
This study aims to determine the effect of legsexercise and HbA1c levels against the value of ABI, Diabetic Peripheral Neuropathy and foot skin moisture in diabetes. The research was conducted with pre-test post-test design without control group. This study with a simple random method, the total sample of 60 people with diabetes in Puskesmas Abiansemal III Badung. Before legs exercise and massage VCO, an average of 8.3 foot sensation and 22.5% skin moisture foot. After legs 0+exercise and massage VCO for 6 weeks, leg sensations average 8.8 and 30.7% skin moisture. MANOVA test showed award legs exercise combined with massage VCO provide the same results with only massage provide VCO or legs exercise, but unlike the humidity foot where leggs exercise combined with massage VCO more effectively.